Class I antiarrhythmic drugs inhibit human cardiac two-pore-domain K+ (K2P) channels - Schmidt, Constanze; Wiedmann, Felix Tobias; Schweizer, Patrick Alexander; Becker, Rüdiger; Katus, Hugo; Thomas, Dierk (European journal of pharmacology, 2013)
Class IC antiarrhythmic drugs are commonly used for rhythm control in atrial fibrillation. In addition, class I drugs are administered to suppress ventricular tachyarrhythmia in selected cases. The multichannel blocking profile of class I compounds includes reduction of cardiac potassium currents in addition to their primary mechanism of action, sodium channel inhibition. Blockade of two-pore-domain potassium (K2P) channels in the heart causes action potential prolongation and may provide antiarrhythmic action in atrial fibrillation. This study was designed to elucidate inhibitory effects of class I antiarrhythmic drugs on K2P channels. Human K2P2.1 (TREK1) and hK2P3.1 (TASK1) channels were systematically tested for their sensitivity to clinically relevant class IA (ajmaline), class IB (mexiletine), and class IC (propafenone) antiarrhythmic compounds using whole-cell patch clamp and two-electrode voltage clamp electrophysiology in Chinese hamster ovary cells and in Xenopus oocytes. Mexiletine and propafenone inhibited hK2P2.1 (IC50,mexiletine=173µM; IC50,propafenone=7.6µM) and hK2P3.1 channels (IC50,mexiletine=97.3µM; IC50,propafenone=5.1µM) in mammalian cells. Ajmaline did not significantly reduce current amplitudes. K2P channels were blocked in open and closed states, resulting in resting membrane potential depolarization. Open rectification properties of the channels were not affected by class I drugs. In summary, class I antiarrhythmic drugs target cardiac K2P K+ channels. Blockade of hK2P2.1 and hK2P3.1 potassium currents provides mechanistic evidence to establish cardiac K2P channels as antiarrhythmic drug targets.
Im Titel ist "+" hochgestellt, "2P" tiefgestellt
Gesehen am 05.07.2021